The inventor : out for blood in Silicon Valley [videorecording (DVD)] - Gibney, Alex (HBO Home Entertainment, 2019)
Academy Award winner Alex Gibney directs a documentary investigating the rise and fall of Theranos, the one-time multibillion-dollar healthcare company founded by Elizabeth Holmes. In 2004, Elizabeth Holmes dropped out of Stanford to start a company that was going to revolutionize healthcare. In 2014, Theranos was valued at